DIALECTIC RELATIONSHIP OF SPIRITUALITY AND MORAL VALUES (Conferencea, 2024)
The article analyzes the philosophical criteria of views on ethics, moral values and moral standards. Also, issues of dialectical connection of spirituality and moral values are highlighted.